PENGARUH RETURN ON ASSET (ROA), EARNING PER SHARE (EPS), DAN NET INTEREST MARGIN (NIM) TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2022 - P. Silaban, Moses; Maharani, Yunita; Shinta Lestari, Deara (Jurnal Akuntansi Bisnis Dan Keuangan, 2024)
This research aims to analyze how much influence Return On Assets (ROA), Earning Per Share (EPS), and Net Interest Margin (NIM) have on share prices in banking companies listed on the Indonesia Stock Exchange for the 2019-2022 period, both partially and simultaneously. The number of samples used in this research were 6 state-owned banking companies listed on the Indonesia Stock Exchange. The type of data is secondary data sourced from financial reports and annual reports. The data analysis method used is the multiple linear analysis method. The results of hypothesis testing show that simultaneously Return On Assets (ROA), Earning Per Share (EPS), and Net Interest Margin (NIM) have a significant effect on stock prices. Partially, Return On Assets (ROA), Earning Per Share (EPS), and Net Interest Margin (NIM) influence stock prices.